Epigenetic modifications in abdominal aortic aneurysms: from basic to clinical - Liu, YuChen; Sun, XiaoYun; Gou, Zhen; Deng, ZhenKun; Zhang, YunRui; Zhao, PingPing; Sun, Wei; Bai, Yang; Jing, YuChen (Frontiers in Cardiovascular Medicine, 2024)
Abdominal Aortic Aneurysm (AAA) is a disease characterized by localized dilation of the abdominal aorta, involving multiple factors in its occurrence and development, ultimately leading to vessel rupture and severe bleeding. AAA has a high mortality rate, and there is a lack of targeted therapeutic drugs. Epigenetic regulation plays a crucial role in AAA, and the treatment of AAA in the epigenetic field may involve a series of related genes and pathways. Abnormal expression of these genes may be a key factor in the occurrence of the disease and could potentially serve as promising therapeutic targets. Understanding the epigenetic regulation of AAA is of significant importance in revealing the mechanisms underlying the disease and identifying new therapeutic targets. This knowledge can contribute to offering AAA patients better clinical treatment options beyond surgery. This review systematically explores various aspects of epigenetic regulation in AAA, including DNA methylation, histone modification, non-coding RNA, and RNA modification. The analysis of the roles of these regulatory mechanisms, along with the identification of relevant genes and pathways associated with AAA, is discussed comprehensively. Additionally, a comprehensive discussion is provided on existing treatment strategies and prospects for epigeneticsbased treatments, offering insights for future clinical interventions.